The RNA Processing Factor Y14 Participates in DNA Damage Response and Repair - Chuang, Tzu-Wei; Lu, Chia-Chen; Su, Chun-Hao; Wu, Pei-Yu; Easwvaran, Sarasvathi; Lee, Chi-Chieh; Kuo, Hung-Che; Hung, Kuan-Yang; Lee, Kuo-Ming; Tsai, Ching-Yen; Tarn, Woan-Yuh (iScience, 2019)
DNA repair deficiency leads to genome instability and hence human disease. Depletion of the RNA processing factor Y14/RBM8A in cultured cells or Rbm8a haplodeficiency in the developing mouse cortex results in the accumulation of DNA damage. Y14 depletion differentially affected the expression of DNA damage response (DDR) factors and induced R-loops, both of which threaten genomic stability. Immunoprecipitation coupled with mass spectrometry revealed DDR factors as potential Y14-interacting partners. Further results confirmed that Y14 interacts with Ku and several DDR factors in an ATM-dependent manner. Y14 co-fractionated with Ku in chromatin-enriched fractions and further accumulated on chromatin upon DNA damage. Y14 knockdown delayed recruitment of DDR factors to DNA damage sites and formation of γH2AX foci and also led to Ku retention on chromatin. Accordingly, Y14 depletion compromised the efficiency of DNA end joining. Therefore Y14 likely plays a direct role in DNA damage repair via its interaction with DDR factors. [Display omitted] •Y14 deficiency leads to DNA damage accumulation•Y14 depletion disturbs DNA damage response and induces R-loops•Y14 promotes Ku70/80 recruitment to DNA damage sites•Y14 participates in DNA damage repair Biological Sciences; Molecular Biology; Cell Biology